Influence of the psd-shell Model with 〖He〗^4 Core and Hartree-Fock Calculations on the Nuclear Structure of 〖Ne〗^20 (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background:A detailed study of the nuclear structure of  has been conducted using the nuclear shell model in conjunction with Hartree-Fock parameterization techniques to provide a deeper understanding of its structural properties. Materials and Methods:The investigation utilized the psd model space along with the PSDMK effective interaction, taking  as an inert core. The model treats the remaining 16 nucleons as active particles interacting within the defined space. Radial wave functions essential for calculating matrix elements were generated using the Hartree-Fock method with various Skyrme force parameterizations, including SkXcsb, SkXta, and SLy4. In addition, harmonic oscillator (HO) wave functions were employed for comparative analysis to evaluate the effect of different single-particle bases on nuclear observables.Results:Several nuclear properties were systematically analyzed, such as longitudinal electron scattering form factors, low-lying energy levels, B(E2) transition strengths, magnetic dipole moments, electric quadrupole moments, root mean square charge radii, and total binding energy.Conclusions:This study emphasizes the benefits of utilizing a  core in shell-model calculations for  by modeling it as a system of five alpha-like clusters. The results indicate that such a cluster-based approach improves theoretical predictions and offers a robust framework for exploring nuclear structure phenomena in light nuclei.